Experimental characterisation of light emission during shock-driven cavity collapse - Anderson, P; Hawker, N; Betney, M; Tully, B; Ventikos, Y; Roy, R (Acoustical Society of America, 2013)
The authors describe experimental work examining the collapse of a cavity by a strong shockwave. A millimetre size cavity is cast in Phytagel, which is then impacted by a metallic projectile accelerated by a compressed gas gun, reaching velocities up to 500 m/s. The impact generates a strong shockwave that propagates into the gel at greater than sonic velocity. Schlieren images are presented that illustrate both this process and the subsequent cavity collapse at a sub-microsecond timescale. As the shockwave reaches the cavity it is shown to cause a rapid asymmetric collapse process characterised by the formation of a high-speed transverse jet. The pressure of the shockwave is found to be 100+ MPa as measured via a custom-built fibre-optic probe hydrophone. Previous work examining shock-driven cavity collapse observed luminescence, postulated to be due to the high-speed impact of the transverse jet on the far bubble wall; this experimental observation is replicated. Further, the light emission is characterised as a function of impact velocity and thus of shockwave pressure. This reveals that shock-driven cavity collapse shares many of the unique features that make the more widely studied SBSL-type collapse interesting.